Analyse de la conformité du matériel audio du livre Tendances A1 avec le plan d'apprentissage semestriel de cours Français Oral Introductif - Wiyar Ageng Mahanani; Ria Fitrasih (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
Listening skills must be mastered first when learning French because by mastering these skills, students will be able to master other language skills. In the French Language Education study program at Universitas Negeri Semarang, one of the courses intended to help students master listening and speaking skills is the Français Orale Introductif. The teaching material used in this course is Tendances A1. It is not yet known whether this teaching material is suitable for the applicable curriculum. Therefore, this research aims to describe the results of the analysis of the suitability of the audio material in Tendances A1 with the semester learning plan for the Français Orale Introductif course. This research uses a qualitative approach with content analysis techniques. Tendances A1 contains nine audio and nine video materials that comply with the RPS of the Français Oral Introductif course. All nine audio materials meet Prastowo's selection criteria for audio teaching materials, while five of the nine video materials that correspond to the RPS for the Français Oral Introductif course meet Prastowo's selection criteria for video teaching materials. As for the themes of descriptions of cultural activities and culinary themes, there is no video or audio material in the Tendances A1 teaching materials that discuss these two themes. These two themes are listed in the semester learning plan for the Français Orale Introductif course.